Pendampingan Penyusunan Laporan Keuangan Bagi Umk Konveksi Ciganitri Bandung - Wardoyo, Dwi Urip; Mahardika, Dewa putra krishna; Fahlevi, Ali riza (Jurnal Pengabdian Masyarakat Akademisi, 2024)
This activity from Community Service (PKM) or known as Abdimas aims to provide understanding to village residents, especially MSEs at Ciganitri Bandung Convection, West Java Province, regarding the importance of preparing simple financial reports for MSEs businesses so that they are easy to understand and implement. The method used in implementing this activity is through mentoring, tutorials and presentations regarding the preparation of financial reports on the EMKM scale. Participants are given a basic understanding and assistance in recording the real financial transactions they face so as to provide understanding, insight and skills in recording transactions and presenting the entity's financial reports. As a result of this community service activity, it is hoped that business actors will be able to independently prepare financial reports for business entities based on generally accepted accounting principles in Indonesia. so that MSE players can provide good and systematic financial information, and can utilize the function of financial reports as a means of obtaining partners and external funding that can support MSE businesses to progress further in the future.